The PacBio Full-Length Transcriptome of the Tea Aphid as a Reference Resource - Hong, Feng; Mo, Si-Hua; Lin, Xing-Yu; Niu, Jinzhi; Yin, Jian; Wei, Dong (Frontiers in Genetics, 2020)
The tea aphid, Aphis aurantii, has become one of the destructive pests in tea plantations in the tropics and subtropics. Very few functional studies have so far focused on the developmental and reproductive biology at a molecular level, because of the lack of comprehensive genetic information. Full-length transcriptomes represent a very highly efficient approach to obtain reference gene sequences in non-model insects. In the present study, the transcriptome of A. aurantii was comprehensively sequenced using PacBio Iso-Seq technology. A total of 46.8 Gb nucleotides and 15,938 non-redundant full-length transcripts were obtained, 13,498 (84.69%) of which were annotated into seven databases. Of these transcripts, 2029 alternative splicing events and 15,223 simple sequence repeats were detected. Among these transcripts, 4,571 (28.68%) and 11,367 (71.32%) transcripts were long non-coding RNAs (lncRNAs) and protein-coding genes, respectively. Five hundred and ninty transcription factors were detected. The first full-length transcriptome represents a significant increase in the known genetic information of A. aurantii. It will assist the future functional study of genes involved in its development and reproduction.